Violet and pansy culture - Bottomly, Helen Elizabeth (My University, 1905)
Introduction: Of all flowers the violet is one of the most popular and widely grown, and is one of which some specie have been cultivated for centuries in Europe. The sweet violet, Piola odorata, is native to Europe and Japan and is now cultivated in its different varieties all over the world for commercial purposes. My experiments with violet seed, however was carried on with the seed of an alpine violet, Viola lutea. This is a rather small plant with leaves much like those of our common silk violet and beans yellow blossoms that have the three lower petals striped with black. For planting the seed, I used flats having spaces between the boards on the bottom in order that the surplus water might drain through instead of making the soil soggy in filling the flats, the first thing put in was a layer of coarse clods to provide drainage, and on this was filled in a mixture of sand, leaf mold and sod, and pressed down until the surface was about an inch below the top of the box, and perfectly level.
Citation: Bottomly, Helen Elizabeth. Violet and pansy culture. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Planting; Watering; Flat Prepared; Theses